Politics of Preferential Development: Trans-global study of affirmative action and ethnic conflict in Fiji, Malaysia and South Africa - Ratuva, Steven (ANU Press, 2013)
The book is a critical examination of affirmative action, a form of preferential development often used to address the situation of disadvantaged groups. -- Provided by publisher.